The Development of Android-Based Basic Services Media to Measure Conceptual Understanding of Adolescents Sexual Behavior - Haka, Nukhbatul Bidayati; Masya, Hardiyansyah; Hamid, Abdul; Citraningrum, Mivtha; Wulandari, Eka (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
This research aimed to find out how the development, feasibility, and effectiveness of android-based guidance and counseling primary service media are used to increase the conceptual understanding of the reproductive system and adolescents sexual behavior during the post-pandemic period. The researchers employed the Borg and Gall’s concept by involving nine stages starting from potential and problem mapping, data collection, product design, design validation, design revision, product trial, product revision, trial use, and product revisions. The research instruments were media expert validation questionnaires, linguists, material experts, student and educator response questionnaires, concept understanding tests, and documentation. The sample used in the limited-scale test was 10 students, while in the wide-scale test there were 76 students. Based on the results of the research on the feasibility test of android-based primary service media on the conceptual understanding of the reproductive system and adolescents sexual behavior, the percentage of material experts was 82%, linguists was 82 %, and media experts was 84 %, all in the very decent category. The results of the questionnaire respondents were very positive in which it was seen from the results of the teacher's response questionnaire that was 94 % and 85 % of students with ‘very interesting’ criteria. Meanwhile, the effectiveness of the media can be seen from the average N-gain of the experimental class 0.58 (moderate) and N-gain of the control class 0.57 (moderate). Independent t-test with a sig 2-tailed 0.00 was less than 0.05 (alpha). Thus, it is concluded that the android can increase the conceptual understanding of the reproductive system and adolescents sexual behavior.